Effects of Fulvic Acid on Photosynthetic Characteristics of Citrus Seedlings Under Drought Stress. Issue 3 (April 2020) - Huang, Shengjia; Xiong, Bo; Sun, Guochao; He, Siya; Liao, Ling; Wang, Jiaqi; Wang, Bozhi; Wang, Zhihui
Abstract: The experimental material in the experiment was citrus seedling of Huangguogan. An experiment was conducted to study the effects of fulvic acid on photosynthetic characteristics of citrus seedlings under drought stress. Portable photosynthesis meter (L1-6400) was used to determine net photosynthetic rate and chlorophyll fluorescence. The results showed that the P n in citrus seedlings spraying with 200, 400, 600 mg ·L -1 fulvic acid was higher than that in control group, which increased with the increase of concentration of fulvic acid. With the increase of fulvic acid concentration, the F o, F m, F v, q P, F v '/ F m ' in PSII and NPQ in citrus seedlings all increased significantly, while the F o /F v in PSII showed an opposite regulation pattern.